Outpatient and Inpatient Single-level Cervical Total Disc Replacement: A Comparison of 30-day Outcomes. Issue 1 (1st January 2019) - Segal, Dale N.; Wilson, Jacob M.; Staley, Christopher; Yoon, S. Tim
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study was to compare 30-day postoperative outcomes between patients undergoing outpatient and inpatient single-level cervical total disc replacement (TDR) surgery. Summary of Background Data: Cervical TDR is a motion-sparing treatment for cervical radiculopathy and myelopathy. It is an alternative to anterior cervical discectomy and fusion (ACDF) with a similar complication rate. Like ACDF, it may be performed in the inpatient or outpatient setting. Efforts to reduce health care costs are driving spine surgery to be performed in the outpatient setting. As cervical TDR surgery continues to gain popularity, the safety of treating patients on an outpatient basis needs to be validated. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried for patients who underwent single-level cervical disc replacement surgery between 2006 and 2015. Complication data including 30-day complications, reoperation rate, readmission rate, and length of stay data were compared between the inpatient and outpatient cohort using univariate analysis. Results: There were 531 (34.2%) patients treated as outpatients and 1022 (65.8%) were treated on an inpatient basis. The two groups had similar baseline characteristics. The overall 30-day complication rate was 1.4% for inpatients and 0.6% for outpatients. Reoperation rate was 0.6% for inpatient and 0.4% for outpatients. Readmission rate was 0.9% and 0.8% for inpatient and outpatient, respectively. There were no statistical differences identified in rates of readmission, reoperation, or complication between the inpatient and outpatient cohorts. Conclusion: There was no difference between 30-day complications, readmission, and reoperation rates between inpatients and outpatients who underwent a single-level cervical TDR. Furthermore, the overall 30-day complication rates were low. This study supports that single-level cervical TDR can be performed safely in an outpatient setting. Level of Evidence: 3 Abstract : The safety of performing outpatient cervical disc replacement surgery has not been validated. The National Surgical Quality Improvement Program database was queried for patients who underwent single-level total disc replacement. There were no statistical differences in rates of readmission, reoperation, or complication between the inpatient and outpatient cohorts.